MYCxing it up with FGFR1 in Squamous Cell Lung Cancer - Lockwood, William (2014)
Recurrent amplification of 8p12 is observed in Squamous Cell Lung Cancer (SQLC) and FGFR1 is thought to be the main oncogenic driver in this region. In this issue of Cancer Discovery, Malchers et al., perform a detailed characterization of 8p12 in SQLC and find remarkable genomic heterogeneity in this region raising the possibility that other genes in addition to FGFR1 may play a role in SQLC. Mechanistic studies of the FGFR1 amplified subset of SQLC revealed potential roles for FGF ligands and MYC expression levels in modulating the response of these tumors to FGFR inhibition.